Protective immune response induced by cationic liposomes bearing soluble antigens improves the survival of BALB/c mice against Toxoplasma gondii RH strain - Hadi Mirahmadi; Ahmad Mehravaran; Mahdi Kavand; Ali Reza Salimi Khorashad; Nasreen Rezaei (Iranian Journal of Basic Medical Sciences)
Objective(s): An ideal strategy to control acute or chronic toxoplasmosis can be the development and production of an effective vaccine. Liposomes as immunoadjuvants may be utilized to boost immune reactions for various antigens.Materials and Methods:  In this study, we encapsulated soluble Toxoplasma antigen (SA) in 1, 2-Dioleoyl-3-trimethylammonium propane (DOTAP) liposomes to assess the elicited immunological response. BALB/C mice received three intramuscular injections of various formulations separated by two weeks. The kind of immune reaction that was created, the degree of protection, the percentage of BALB/c mice that survived the Toxoplasma gondii challenge, the immune reaction assessment with cytokine synthesis (IFN-γ, IL-4), and the titration of IgG isotypes were all evaluated.Results: Compared to other groups, the liposome DOTAP + imiquimod + SA-immunized mice showed a significantly lower death rate (P<0.01). Liposome DOTAP + Imiquimod + SA had higher IgG2a and IFN-γ secretion levels than the control group (P<0.001 and P<0.0001, respectively).Conclusion: According to the study’s findings, the liposome DOTAP + imiquimod + SA formulation generates a cellular immunological response, making it resistant to the T. gondii challenge.